2019
DOI: 10.1002/qre.2560
|View full text |Cite
|
Sign up to set email alerts
|

A new nonparametric double exponentially weighted moving average control chart

Abstract: There are many practical situations where the underlying distribution of the quality characteristic either deviates from normality or it is unknown. In such cases, practitioners often make use of the nonparametric control charts. In this paper, a new nonparametric double exponentially weighted moving average control chart on the basis of the signed-rank statistic is proposed for monitoring the process location. Monte Carlo simulations are carried out to obtain the run length characteristics of the proposed cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…It showed that a fast initial response (FIR) feature is useful for the (EWMA) chart, especially for small values of smoothing constants. Raza [7] proposed a new (EWMA) control chart based on (SC) statistic that the area below the straight line is a control area that makes the control method simpler than other methods and can detect the source and direction of the change that occurs during the sampling period. Each of them found that this chart was more efficient than the Shewhart chart in detecting random deviations that occur during the production processes.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that a fast initial response (FIR) feature is useful for the (EWMA) chart, especially for small values of smoothing constants. Raza [7] proposed a new (EWMA) control chart based on (SC) statistic that the area below the straight line is a control area that makes the control method simpler than other methods and can detect the source and direction of the change that occurs during the sampling period. Each of them found that this chart was more efficient than the Shewhart chart in detecting random deviations that occur during the production processes.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a nonparametric EWMA chart with integer‐valued weights for monitoring the location parameter and it is seen its superiority against the CUSUM, EWMA, and GWMA sign charts in moderate to large shifts. Raza et al 19 . developed a nonparametric DEWMA chart based on the signed‐rank statistic to improve the performance of the EWMA signed‐rank chart.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chen et al 30 developed the GWMA‐SN chart based on repetitive sampling (RS‐SWMA‐SN) to improve the performance of the GWMA‐SN chart in detecting small shifts. Raza et al 31 proposed the DEWMA signed‐rank (DEWMA‐SR) chart, and they showed that it outperforms the EWMA‐SN, EWMA‐SR, and DEWMA‐SN charts. Nonparametric GWMA and DGWMA charts were also developed in the case where the IC process median is unknown in advance (see Chakraborty et al 32 and Karakani et al 33 ).…”
Section: Introductionmentioning
confidence: 99%